Development of Asahan River Tourism Activities in Support of National Tourism Strategic Area of Lake Toba - Mega Fitriani Adiwarna Prawira; Beta Budisetyorini; Deddy Adisudharma; Dicky Arsyul Salam; Wisi Wulandari; Eko Susanto (Politeknik Negeri Bandung, 2021)
Following up on the Development of The National Tourism Strategic Area of Lake Toba, which was directed in the study